(untitled) (Open Access Indonesian Journal of Medical Reviews, 2025)
Spindle cell carcinoma (SpCC) of the lung is a rare and aggressive subtype of non-small cell lung carcinoma (NSCLC), characterized by a significant component of spindle-shaped tumor cells. Its radiological presentation is highly variable, typically appearing as peripheral or central lung masses. Presentation as a primary mediastinal mass is exceedingly uncommon, posing a considerable diagnostic challenge. A 47-year-old woman presented with a 4-month history of progressive lower limb weakness. Initial chest radiography revealed a left-sided mediastinal-appearing mass. Subsequent contrast-enhanced computed tomography (CT) of the thorax characterized a large, lobulated soft tissue mass in the left posterior mediastinum, measuring 5.25 × 4.74 cm. The mass exhibited homogeneous isodensity with peripheral calcification, caused 0.5 cm compression of the descending aorta, and showed erosion of the 4th thoracic vertebra with contrast enhancement. Fine needle aspiration (FNA) cytology, guided by CT, demonstrated atypical, polymorphic spindle-shaped cells within a fibroangiomatous stroma, consistent with spindle cell carcinoma. In conclusion, this case highlights an unusual presentation of pulmonary SpCC mimicking a posterior mediastinal tumor with aggressive features, including vascular compression and vertebral erosion. Despite its mediastinal appearance, subtle radiological signs such as the acute angle with the lung parenchyma, the epicenter of the mass, and the irregular tumor-lung interface suggested a pulmonary origin. This report underscores the importance of meticulous radiological evaluation and cytopathological correlation in diagnosing rare lung cancer variants that can masquerade as primary mediastinal neoplasms.